2014
DOI: 10.1108/jocm-03-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Examining entrepreneurial intention through cognitive approach using Malaysia GEM data

Abstract: Purpose – The purpose of this paper is to explore entrepreneurial intentions among Malaysia adult population through the cognitive approach model. Design/methodology/approach – This paper is based on Global Entrepreneurship Monitor nation-wide survey which includes questions about entrepreneurial perceptions of the country's population. Findings – Three kinds of perceptions are id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…The Nagelkerke R2 or pseudo-R2 statistics provide an indication of the amount of variation in the independent variable explained by the model (Ahmad et al, 2014). In Model 1, only 20.0 of the variability is explained by the demographic and socioeconomic variables.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nagelkerke R2 or pseudo-R2 statistics provide an indication of the amount of variation in the independent variable explained by the model (Ahmad et al, 2014). In Model 1, only 20.0 of the variability is explained by the demographic and socioeconomic variables.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Similarly, they found males to be more enthusiastic about business ownership than females (Schwarz et al, 2009). Furthermore, Ahmad, Xavier, and Bakar (2014) found that respondents in the upper secondary are highly associated with higher EI. Individuals with a high level of education tend to show a greater propensity towards entrepreneurship (Liñ an, Rodr ıguez-Cohard, & Rueda-Cantuche, 2011; Turker & Selcuk, 2009) because they are likely to be able to identify an opportunity to start a new business (Hui-Chen, Kuen-Hung, & Chen-Yi, 2014).…”
Section: Entrepreneurial Intention and Demographics And Socio-economimentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, the interest of the researchers for the issue of entrepreneurship and entrepreneurial intentions is evident (Staniewski & Awruk, 2016;Staniewski & Szopi nski, 2015). The question that separates those who choose to engage in entrepreneurship from those who do not is the interest of researchers (Ahmad, Xavier, & Bakar, 2014). Entrepreneurship begins when an individual deciding to start a business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors consider education an important predictor of entrepreneurial intention, whether it is the education level (Ahmad et al, 2014), educational background (Kristiansen & Indarti, 2004), the perception of the education system and the quality of education (Belas et al, 2017), or entrepreneurial education (Rokhman & Ahamed, 2015), education major (Solesvik, 2013), and knowledge acquired (Liñ an, Rodr ıguez-Cohard, et al, 2011). Gelard and Saleh (2011), among other support types, included educational support in their model considering it as professional education in universities as an efficient way of obtaining necessary knowledge about entrepreneurship.…”
Section: Entrepreneurial Intention and Entrepreneurial Capacitymentioning
confidence: 99%